2002
DOI: 10.1038/sj.onc.1205818
|View full text |Cite
|
Sign up to set email alerts
|

Three isoforms of annexin I are preferentially expressed in normal esophageal epithelia but down-regulated in esophageal squamous cell carcinomas

Abstract: The development and progression of human cancer are believed to be due to the alterations of multiple genes or/ and their protein products. For identifying the proteins associated with esophageal cancer, we analysed the protein profiles of 24 pairs of esophageal squamous cell carcinomas/matched adjacent normal epithelia. Microdissection of routinely unstained frozen sections was performed to purify cancerous and epithelial cells. The protein expression profiles were obtained by twodimensional electrophoresis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 19 publications
(13 reference statements)
1
73
0
1
Order By: Relevance
“…Western blotting and immunohistochemical analysis showed a drastic decrease or complete loss of ANXA1 levels in esophageal tumors and high-grade dysplasia when compared to the paired normal epithelium, implying that ANXA1 plays a functional role in maintaining the normal status of esophageal epithelium (Paweletz et al, 2000). A comparative protein profiling study also identified lower ANXA1 protein levels in esophageal carcinomas than in the paired normal epithelia (Xia et al, 2002). In their study, ANXA1 levels were found to be suppressed in 75% of welldifferentiated, 94% of moderately differentiated and 100% of the poorly differentiated tumors analysed, thus correlating with the extent of tumor differentiation.…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…Western blotting and immunohistochemical analysis showed a drastic decrease or complete loss of ANXA1 levels in esophageal tumors and high-grade dysplasia when compared to the paired normal epithelium, implying that ANXA1 plays a functional role in maintaining the normal status of esophageal epithelium (Paweletz et al, 2000). A comparative protein profiling study also identified lower ANXA1 protein levels in esophageal carcinomas than in the paired normal epithelia (Xia et al, 2002). In their study, ANXA1 levels were found to be suppressed in 75% of welldifferentiated, 94% of moderately differentiated and 100% of the poorly differentiated tumors analysed, thus correlating with the extent of tumor differentiation.…”
Section: Introductionmentioning
confidence: 71%
“…In esophageal cancers, several published reports confirm that the loss of ANXA1 is an early event in tumorigenesis (Paweletz et al, 2000;Xia et al, 2002;Hu et al, 2004). Western blotting and immunohistochemical analysis showed a drastic decrease or complete loss of ANXA1 levels in esophageal tumors and high-grade dysplasia when compared to the paired normal epithelium, implying that ANXA1 plays a functional role in maintaining the normal status of esophageal epithelium (Paweletz et al, 2000).…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations